Solar Fresnel modelling, geometry enhancement and 3D ray tracing analysis devoted to different energy efficiency definitions and applied to a real facility. (1st March 2021) - Fossa, Marco; Boccalatte, Alessia; Memme, Samuele
Highlights: New in-house 3D model for raytracing analyses of Linear Fresnel Collectors. Study of the optical and energy efficiency of a real Fresnel plant. Plant geometry optimization considering gap between mirrors and receiver height. Maximization of the radiant energy arriving at the receiver aperture area. Optimum value of the receiver height is not unique all over the year. Abstract: Despite their few installations, Linear Fresnel Collectors (LFC) represent a very promising technology for efficient solar energy exploitation at medium to high temperatures thanks to their lowest land area per electric energy ratio. Their first appearance was in the '60, thanks to Professor Giovanni Francia realizations at the University of Genova, Italy. This research aims to determine the performance of a LFC and perform parametric studies through 3D ray-tracing simulations. The in-house developed code accounts for all geometrical parameters of the mirrors and receiver assembly, including mirror dimensions, curvature and distance, primary mirror optical errors, receiver aperture area and elevation, secondary mirror compound parabolic shape. The present study includes a detailed investigation on shading, blocking and end effect issues while introducing 6 different different optical and energy efficiency definitions. A parametric analysis is applied to the distance between mirrors and the receiver height. After the code validation against Tonatiuh, the calculations are performed to analyse in details the performance of a real LFC plant in Morocco. The peak optical efficiency of the test case plant has been estimated up to 87% but it is demonstrated the selection of the efficiency definition is crucial for performing successful geometry optimizations.